Durability of Concrete with Man-made Thermoplastic Sulfur Additive. Issue 3 (June 2020) - Gumeniuk, Aleksandr; Hela, Rudolf; Polyanskikh, Irina; Gordina, Anastasia; Yakovlev, Grigorij
Abstract: In the article, the data on sulfur surface modification and its influence on the properties of common cement mix and concrete are discussed as well as durability and corrosive resistance of modified compositions. The composite components, conditions of mixtures making, and required temperature treatment were established in the laboratory testing. The potentiometric model was used to assess the interaction between the corrosive environment and the modified composites, a corrosive agent being used as a sulfate environment. This model takes into account the change in reaction potentials and is used as an index of the solvolysis reaction between the sulfate solution and constituents of the modified cement matrix. This modelling determined two main characteristics used to predict the durability of building material. These are the depth of corrosive agent in the material structure and the amount of solved calcium hydroxide. The established data show the potential usefulness of the modified additive based on man-made sulfur as an additive for cement composites. The modified additive can be used for materials with a high performance and durability in an aggressive environment. The increasing of corrosive resistance might be explained by the structure changing and by the properties of the formed crystalline hydrates.